The Emotional Overdraft 10 Simple Changes for Balancing Business Success and Wellbeing - Brown, Andy (Practical Inspiration Publishing, 2024)
It is possible to run a successful business without sacrificing either your mental or physical health. The Emotional Overdraft will show you how to eliminate the ten behaviours that are holding you and your business back